Rejection of intestinal allotransplants is driven by memory T helper type 17 immunity and responds to infliximab. Issue 3 (25th September 2020) - Kroemer, Alexander; Belyayev, Leonid; Khan, Khalid; Loh, Katrina; Kang, Jiman; Duttargi, Anju; Dhani, Harmeet; Sadat, Mohammed; Aguirre, Oswaldo; Gusev, Yuriy; Bhuvaneshwar, Krithika; Kallakury, Bhaskar; et al.
Abstract : Intestinal transplantation (ITx) can be life‐saving for patients with advanced intestinal failure experiencing complications of parenteral nutrition. New surgical techniques and conventional immunosuppression have enabled some success, but outcomes post‐ITx remain disappointing. Refractory cellular immune responses, immunosuppression‐linked infections, and posttransplant malignancies have precluded widespread ITx application. To shed light on the dynamics of ITx allograft rejection and treatment resistance, peripheral blood samples and intestinal allograft biopsies from 51 ITx patients with severe rejection, alongside 37 stable controls, were analyzed using immunohistochemistry, polychromatic flow cytometry, and reverse transcription‐PCR. Our findings inform both immunomonitoring and treatment . In terms of immunomonitoring, we found that while ITx rejection is associated with proinflammatory and activated effector memory T cells in the blood, evidence of treatment efficacy can only be found in the allograft itself, meaning that blood‐based monitoring may be insufficient. In terms of treatment, we found that the prominence of intra‐graft memory TNF‐α and IL‐17 double‐positive T helper type 17 (Th17) cells is a leading feature of refractory rejection. Anti–TNF‐α therapies appear to provide novel and safer treatment strategies for refractory ITx rejection; with responses in 14 of 14 patients. Clinical protocols targeting TNF‐α, IL‐17, and Th17 warrant further testing. Abstract : This study elucidates the critical role of Th17 cells in intestinal transplant rejection and proposes new clinical approaches for immunomonitoring and treatment of refractory rejection.